Quo Vadis PCA? A Review on Current Concepts, Economic Considerations, Patient-Related Aspects, and Future Development with respect to Patient-Controlled Analgesia - S. Nardi-Hiebl; L. H. J. Eberhart; M. Gehling; T. Koch; T. Schlesinger; P. Kranke (Anesthesiology Research and Practice)
This review assesses four interrelating aspects of patient-controlled analgesia (PCA), a long-standing and still widely used concept for postoperative pain management. Over the years, anaesthesiologists and patients have appreciated the benefits of PCA alike. The market has seen new technologies leveraging noninvasive routes of administration and, thus, further increasing patient and staff satisfaction as well as promoting safety aspects. Pharmaceutical research focuses on the reduction or avoidance of opioids, side effects, and adverse events although influence of these aspects appears to be minor. The importance of education is still eminent, and new educational formats are tested to train healthcare professionals and patients likewise. New PCA technology can support the implementation of efficient processes to reduce workload and human errors; however, these new products come with a cost, which is not necessarily reflected through beneficial budget impact or significant improvements in patient outcome. Although first steps have been taken to better recognize the importance of postoperative pain management through the introduction of value-based reimbursement, in most western countries, PCA is not specifically compensated. PCA is still an effective and valued technique for postoperative pain management. Although there is identifiable potential for future developments in various aspects, this potential has not materialized in new products.